Adolescents' self-reported motor assessments may be more realistic than those of their parents. (April 2018) - Timler, Amanda; McIntyre, Fleur; Hands, Beth
Introduction: Adolescents' motor competence influences their physical, social and emotional development. Parent-reported assessments may not be truly representative of their adolescent's motor difficulties. This study examined the congruency between parent- and self-reported motor competence in 133 parent-adolescent dyads. Method: The adolescent-reported Adolescent Motor Competence Questionnaire (AMCQ; ≤83) and the parent-reported Developmental Coordination Disorder Questionnaire 2007 (DCDQ-07; ≤57) cut scores classified 133 (Mage = 14.5 years) adolescents into high and low motor competence. Parents also completed the Swanson, Nolan and Pelham IV (SNAP-IV) for descriptive purposes. Findings: A moderate correlation ( r = 0.56, P < 0.001) was found between the AMCQ and the DCDQ-07 scores. Overall, 42 low motor competence cases were identified by both measures (AMCQ and DCDQ-07). Parents identified more boys (11) than girls (9) with low motor competence, whereas more female adolescents (22) self-reported low motor competence than boys (18). A high proportion agreement (0.82) was seen, which was principally due to the 91 (68.4% of sample) high motor competence case agreements. Conclusion: Parents identified fewer motor difficulties in their adolescent, especially for girls. Self-report motor assessments may be more realistic for adolescents as they are aware of their own capabilities. Such measures are also more likely to identify previously undiagnosed adolescents with low motor competence.